Introduction to scholastic theology - Leinsle, Ulrich Gottfried; Miller, Michael J. (Washington, District of Columbia : Catholic University of America Press, 2010)
There are a number of overviews of scholastic philosophy in print, all of which focus either on one stream of thought, one denomination, or one time period. With this book, distinguished historian of philosophy Ulrich Leinsle offers the first comprehensive introduction to scholastic theology a textbook for both Protestant and Catholic students.
Reading Introduction to Scholastic Theology is an adventure, as it guides readers through the beginnings of scholastic theology in the works of the Fathers, on to Early Scholasticism, High Scholasticism, scholastic thought in a time of paradigm shifts (14-15th century) and its fate during Humanism and Reformation, to the beginnings of the Enlightenment, and Neo-Scholasticism in the nineteenth century. --Book Jacket.
Introduction: What Is Scholastic Theology? : -- 1. On the history of the concept "Scholasticism" -- 2. Attempts at a definition -- 3. Characteristics -- 4. Scholastic theology -- I. How Did Scholastic Theology Come About? : -- 1. Patristic themes and methods -- 1.1. Philosophy and theology -- 1.2. Auctoritas and ratio -- 1.3. Augustine's program of Christian education and theology -- 1.4. Systematic and axiomatic theology: Boethius --1.5. Collections of sentences: Isidore of Seville -- 2. Scholastic theology: Methods and presentation -- 2.1. Development of the schools, curriculum, and the liberal arts -- 2.2. Instructional procedure -- 2.3. The Bible and Scholastic theology -- 2.4. Collections of sentences and Summas -- 2.5 Theological systematization -- 2.6. Treatise and letter -- 2.7. The Scholastic sermon -- 2. The Self-Concept of Early Scholastic Theologies : -- 1. Freedom from contradiction and theological truth: Duns Scotus Eriugena -- 2. Faith seeking understanding: Anselm of Canterbury -- 3. Systematic treatment of patristic sentences: The school of Laon -- 4. Theology as wisdom and way of life: Hugh of St. Victor -- 5. Theology as linguistic criticism: Peter Abelard -- 6. The metaphysical grammar of discourse about God: Gilbert Porreta -- 7. The textbook: The Sentences of Peter Lombard -- 8. Axiomatic theology -- 9. Towards a standard theological language -- 10. Scholastic and monastic theology -- 11. Learned heresy -- 3. Theology as a Science at the University : -- 1. The university as the home of theology -- 1.1. University organization, teaching activity, and presentational forms -- 1.2. The mendicant orders at the universities -- 1.3 Biblical or systematic theology? -- 2. Aristotle as a challenge to theology -- 2.1. A new scientific model -- 2.2. A pagan view of the world and man -- 2.3. The influence of non-Christian syntheses -- 2.4. The Church's reaction: The prohibition of Aristotle -- 2.5. Theological truth and the truths of the natural sciences -- 2.6 The condemnations of 1270 and 1277 -- 3 The scientific character of theology -- 3.1. Faith and argument: William of Auxerre -- 3.2. Between Bible and science: The early Dominicans -- 3.3. Salvation history or metaphysics: The Summa Halensis -- 3.4. Presuppositions and goal of theological science: Albert the Great -- 3.5, Theology as science and wisdom in Christ: Bonaventure -- 3.6. A proof of scientific character? Thomas Aquinas -- 3.7. The Franciscan reaction: William de la Mare -- 3.8. Immunization through "enlightenment": Henry of Ghent -- 3.9 Augustinian or Aristotelian science? Ægidius Romanus -- 4. Theological Controversy and Church Reform : -- 1. Scholastic theology amid societal upheaval -- 1.1. The development of academic study -- 1.2. Formation of schools and the dispute about the two ways -- 1.3. Theology, Church, and society: Wycliffe and Hus -- 1.4. Toward a biblical and affective theology: Johannes Gerson -- 1.5 University theology and spiritual direction for aristocratic ladies: Vienna -- 1.6. Scholastic criticism of devotio moderna and Reform theology -- 2. Theological certainty in an uncertain age? -- 2.1 Human action in the knowledge of God: Duns Scotus -- 2.2. Assuring human statements about God: Francis of Meyronnes -- 2.3. Axiomatic metaphysics as the foundation of theology: Meister Eckhart -- 2.4 What can we know?: William of Ockham -- 2.5. Propositional logic of the faith: Robert Holcot -- 2.6. What can we do?: Gregory of Rimini -- 2.7. God's knowledge and human freedom: Marsilius of Inghen -- 2.8. How do I find a gracious God?: Gabriel Biel -- 5. Humanist and Reformation Theology : -- 1. University, humanism, and Reformation -- 1.1. Reformatio studii: Wish and reality -- 1.2. Biblical-humanist reform of theology: Erasmus of Rotterdam -- 1.3. University theology and Reformation: Disputatio -- 2. Approach to theology in Reformed Christianity -- 2.1. "Contra scholasticam theologiam": Martin Luther -- ) 2.2. The new "Summa": Melanchthon's "Loci theologici" -- 2.3. Summa of self-knowledge and practical knowledge about God: Calvin -- 3. The Catholic understanding of theology -- 3.1. Humanist reform of Scholasticism and controversy: Johannes Eck -- 3.2. Cajetan and the new Thomism -- 6. Scholastic Theology: Early Modern Period : -- 1. Development and presentational forms -- 1.1. The university as a territorial and confessional institution for education -- 1.2. Catholic theology after the Council of Trent -- 1.3. Scholastic and positive theology -- 1.4. The development of schools of Catholic theology -- 1.5. Presentational forms -- 2. The "Scholasticism" of Protestant orthodoxy -- 2.1. From creed to theological system -- 2.2. Concept of theology in early Lutheran Orthodoxy: Johann Gerhard -- 2.3. Anti-Scholastic "Scholasticism": Abraham Calov -- 2.4. Theology in one sentence: Johann Adam Scherzer -- 2.5. Theology within the framework of the encyclopedia: Johann Heinrich Alsted -- 2.6. Reformed "Cartesian Scholasticism": Christoph Wittich -- 3. God and modern man: The debate about grace -- 3.1. Man as a free instrument of God: Francisco Suárez -- 3.2. Natural morality or the effect of grace?: Gabriel Vázquez -- 3.3. God's decision and man's freedom: Bartolomeo Mastri -- 3.4. God's knowledge dependent on free human beings: Rodrigo de Arriaga -- 3.5. Thomistic opposition to the scientia media: Jean-Baptiste Gonet -- 3.6. Causal-metaphysical predetermination of the will: Ludwig Babenstuber -- 4. The difficult assimilation of the new -- 4.1. Caramuel and the Galileo case -- 4.2. Cartesian teaching on the Eucharist: Robert Desgabets -- 4.3. Eclectic theology: Eusebius Amort -- 7. Prospect: Enlightenment and New Scholasticism.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Scholasticism -- History; Scolastique -- Histoire; RELIGION -- Christian Theology -- History; RELIGION -- Christian Theology -- Systematic; RELIGION -- Christianity -- General; Scholasticism; History